Introduced species in Flora of Libya 1 - K. Alzerbia, Abdulhamid; A. Alaibb, Mohamed; Omar, Naser (Libyan Journal of Science &Technology, 2022)
Introduced Species in Flora of Libya were reported in this study, the results showed of 361 species of introduced plants (17.72%) from the species recorded in the flora of Libya. These species belong to 253 genera and 89families. Six of these families belong to gymnosperms and the rest belong to angiosperms. The recorded species were introduced for different purposes, such as food, fodder, ornamental, and windbreaks. These species established and become part of the Libyan flora. Some of which are poisonous to humans or animals and some are a strong competitor or allopathic to local plants. In this paper, a list of introduced species, the origin of these species, and the purpose of their introduction will be included.